Pond dyes are Culex mosquito oviposition attractants - Natali Ortiz Perea; Amanda Callaghan (PeerJ, 2017)
Background British mosquito population distribution, abundance, species composition and potential for mosquito disease transmission are intimately linked to the physical environment. The presence of ponds and water storage can significantly increase the density of particular mosquito species in the garden. Culex pipiens is the mosquito most commonly found in UK gardens and a potential vector of West Nile Virus WNV, although the current risk of transmission is low. However any factors that significantly change the distribution and population of C. pipiens are likely to impact subsequent risk of disease transmission. Pond dyes are used to control algal growth and improve aesthetics of still water reflecting surrounding planting. However, it is well documented that females of some species of mosquito prefer to lay eggs in dark water and/or containers of different colours and we predict that dyed ponds will be attractive to Culex mosquitoes. Methods Black pond dye was used in oviposition choice tests using wild-caught gravid C. pipiens. Larvae from wild-caught C. pipiens were also reared in the pond dye to determine whether it had any impact on survival. An emergence trap caught any adults that emerged from the water. Water butts (80 L) were positioned around university glasshouses and woodland and treated with black pond dye or left undyed. Weekly sampling over a six month period through summer and autumn was performed to quantified numbers of larvae and pupae in each treatment and habitat. Results Gravid female Culex mosquitoes preferred to lay eggs in dyed water. This was highly significant in tests conducted under laboratory conditions and in a semi-field choice test. Despite this, survivorship in black dyed water was significantly reduced compared to undyed water. Seasonal analysis of wild larval and pupal numbers in two habitats with and without dye showed no impact of dye but a significant impact of season and habitat. Mosquitoes were more successful, with significantly higher numbers of pupae, in the habitat where they had vegetation cover and shade. Discussion Our study has raised some interesting possibilities; one is that where used, pond dyes may be encouraging mosquitoes to breed in gardens in close proximity to people. Considering the concerns over potential future spread of disease in urban environments, this as well as shading of ponds and water butts, should inform future advice over reducing mosquito breeding and spread.